Dynamic Adaptive Streaming Algoritbm in ICN - Yonghui Xin; Yang Li; Tao Lin (Dianxin kexue)
Information-centric networking（ICN）has different type of router node from the traditional network, which has caching facilities, and popular content will be pushed to the edge of the network closer to the user, reducing the delay of the user's access to the content. However, ICN's caching will result in the shake or even the interruption of video play when client uses the traditional adaptive streaming protocol, reducing the user's viewing experience. An algorithm for dynamic adaptive streaming in ICN was proposed, ensuring smoothly playback as well as improving the average bitrate of play thus to enhance the user's viewing experience. Simulation experiment on the existing ICN platform proves that the adaptive algorithm performs better than the traditional algorithms.